Comparative study of open approach and laparoscopic surgery for emergent groin hernias - Kurumiya, Yasuhiro; Mizuno, Keisuke; Sekoguchi, Ei; Sugawara, Gen (International Surgery Journal, 2019)
Background: The utilization of laparoscopic surgery for groin hernias is rapidly increasing in Japan even though a consensus for the use of the laparoscopic over the open approaches to surgery for emergent cases has yet to be determined. Therefore, we retrospectively examined patient outcomes from both open and laparoscopic surgeries. Methods: Emergent surgery for a strangulated groin hernia was performed on 63 patients at our hospital from January 2013 to December 2017. All laparoscopic surgeries were performed using the transabdominal preperitoneal repair (TAPP) approach. The choice of whether to perform an open approach (open) or laparoscopic surgery with the TAPP approach was made by doctors who were familiar with both surgical techniques. Results: There were 49 patients in the open group and 14 patients in the TAPP group. The median operation time (min) was 78 in the open group and 127 in the TAPP group. The median intraoperative blood loss (ml) was 21.0 in the open group and 3.0 in the TAPP group. There were 12 patients (24.5%) in the open group and 1 patient (7.1%) in the TAPP group who had postoperative complications. Surgical site infection did not occur in the TAPP group. Conclusions: TAPP is a useful technique in emergent surgery for incarcerated hernias.